Novel prognostic value and potential utility of opioid receptor gene methylation in liquid biopsy for oral cavity cancer - Ishikawa, Ryuji; Imai, Atsushi; Mima, Masato; Yamada, Satoshi; Takeuchi, Kazutaka; Mochizuki, Daiki; Shinmura, Daichi; Kita, Jun-ya; Nakagawa, Takuya; Kurokawa, Tomoya; Misawa, Yuki; Nakanishi, Hiroshi; et al. (Current problems in cancer, 2022)
Opioids are a class of recreational drugs and prescription medications that bind to a group of G-protein-coupled receptors known as opioid receptors (ORs). ORs are involved in the development of many types of cancer; however, their role in head and neck squamous cell carcinoma (HNSCC) is complex and poorly understood. Here, we analyzed the methylation status of five OR genes in verification (301 HNSCC primary samples) and validation (five circulating tumor DNA [ctDNA] samples) studies using quantitative methylation-specific PCR (Q-MSP). OPRL1 and OPRM1 methylation levels were significantly higher in HNSCC tissues than in corresponding normal tissues from the same individuals (P = 0.001 and P < 0.001, respectively). In Kaplan-Meier estimate and multivariate Cox proportional hazard analyses, two genes (OPRL1 and OPRM1) were significantly associated with increased recurrence in the methylation group with oral cavity cancer. Furthermore, a validation study of ctDNA demonstrated that OPRL1 genes exhibited predictive performance as emerging biomarkers and were each capable of discriminating the plasma from tumor-free individuals. We characterized the relationship between OR gene methylation status and outcomes in oral cavity cancer. Our results highlight the potential utility of ctDNA methylation-based detection in the clinical management of oral cavity cancer.